2018
DOI: 10.1109/tcomm.2018.2840713
|View full text |Cite
|
Sign up to set email alerts
|

Communication with Crystal-Free Radios

Abstract: We consider a communication channel where there is no common clock between the transmitter and the receiver. This is motivated by the recent interest in building system-onchip radios for Internet of Things applications, which cannot rely on crystal oscillators for accurate timing. We identify two types of clock uncertainty in such systems: timing jitter, which occurs at a time scale faster than the communication duration (or equivalently blocklength); and clock drift, which occurs at a slower time scale. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In closing, we note that problems related to the one studied in this letter are also of interest in communication engineering, where they have been explored in the context of synchronization errors such as the so-called clock-drift; see, e.g., [9,10]. * kmladen@uns.ac.rs…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In closing, we note that problems related to the one studied in this letter are also of interest in communication engineering, where they have been explored in the context of synchronization errors such as the so-called clock-drift; see, e.g., [9,10]. * kmladen@uns.ac.rs…”
Section: Discussionmentioning
confidence: 99%
“…Optimal codes for a model equivalent to ours (where, instead of relativistic time dilation, the signal distortion is caused by the so-called "clock drift") have been determined in [9] for the cases γ ∈ [1, γ] and γ ∈ [1, ∞). We next describe these codes, as well as the optimal codes for the remaining cases γ ∈ [1, γ), γ ∈ (1, γ), and γ ∈ (1, γ],…”
Section: Optimal Codes and Their Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Application domains include activity trackers, wearables, smart materials, factory automation, in-body and personal health monitoring, and microrobots. To be able to scale to trillions of deployed wireless devices [1], they need to be small and cheap. This is the primary motivation for designing radios that do not require any external components [2].…”
Section: Introductionmentioning
confidence: 99%
“…Wireless communication systems (''radio chips'') have been demonstrated that are as small as 0.46 mm 2 [14], 2.025 mm 2 [15], ≈ 4.4 mm 2 [16], ≈9 mm 2 [17]. As a point of comparison, the area occupied by a small crystal oscillator is ≈2 mm 2 [1], [4].…”
Section: Introductionmentioning
confidence: 99%